Media education in higher education institutions in Ecuador - Mena, David Leonardo Proaño; Andrango, Diana Valeria Chango; Caguana, Jonathan Mauricio Guallpa; Caguana, Willian Edmundo Guallpa (Journal of Posthumanism, 2025)
This paper examines media literacy education in higher education institutions in Ecuador, addressing its impact on the teaching-learning process and the development of critical skills in students. The text undertakes an analysis of the evolution of media literacy education, emphasizing its role in the development of cognitive, intellectual, and ethical skills. Furthermore, it offers a comprehensive perspective on how institutions of higher education can adapt their pedagogical approaches to promote media literacy and prepare students for a dynamic digital environment. The study underscores the necessity to cultivate critical, reflective, and communicative competencies in the utilization of media tools, thereby advocating for comprehensive training for prospective professionals.